Implementation of Digital Educational Technology in Thematic Learning for Children at Tadika Al-Fikh Orchard Malaysia - Setiawan, Hasrian Rudi; Hasan, Ibrahim; Haryani, Nadia Dwi (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to improve the quality of thematic learning for early childhood through the implementation of digital educational technology at Tadika Al-Fikh Orchard Malaysia. The program involved training and mentoring teachers in utilizing various interactive digital media such as educational videos, Android-based learning applications, and interactive visual tools. The implementation method included initial observation, training sessions, digital media development workshops, and classroom application evaluations. The results showed that teachers were able to use digital technology effectively in thematic learning, which positively impacted children’s motivation, participation, and understanding of learning materials. Therefore, the implementation of digital educational technology serves as an innovative strategy to support enjoyable and meaningful learning experiences for early childhood.